Tackling cyberbullying: review of empirical evidence regarding successful strategies - Perren, S. (2017)
A summary of current knowledge on successful responses to cyberbullying differentiating between three different response domains: reducing risks, combatting the problem, and buffering negative impact. A systematic literature search yielded thirty-six relevant studies, most of which report findings regarding general prevention strategies (e.g., anti-bullying policies or cybersafety strategies) and the use of coping strategies such as seeking support, responding (retaliation or confronting), technical solutions, and avoidant and emotion-focussed strategies. Whilst a few studies report perceived success, very few measure the success of the strategies in relation to risks and outcomes. There is a clear lack of evidence concerning successful responses.